2013
DOI: 10.1097/prs.0b013e3182865bf5
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoacromial Artery Perforator Flap

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Knowledge of the location, morphology, and variations of the TAT and its branches may be of great importance in plastic and reconstructive surgeries. Zhang et al presented an extensive study providing evidence of the vascular supply and the clinical application of the perforator flap of the thoracoacromial artery [ 18 ]. In the study, both cadaveric and clinical investigations of the TAT were carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the location, morphology, and variations of the TAT and its branches may be of great importance in plastic and reconstructive surgeries. Zhang et al presented an extensive study providing evidence of the vascular supply and the clinical application of the perforator flap of the thoracoacromial artery [ 18 ]. In the study, both cadaveric and clinical investigations of the TAT were carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described this type of flap as a good choice for the repair of tracheal defects due to its short harvest time, thin thickness, and stable blood supply [ 1 ]. Zhang et al presented a cadaveric and clinical study on the potential clinical application of the TAT perforator flap [ 18 ]. The authors of the study found a constant TAT perforator in the septum of the clavicular and sternocostal heads of the pectoralis major muscle in 21 of 24 hemichests.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Certain areas of these regions are used as donors in clinical practice for reconstruction surgeries of the head and neck, as well as radical mastectomies. [4][5][6][7][8][9] In case of injuries of the anterior chest wall, the AA and its branches may also be involved, which may also require surgical intervention. [3][4][5][6][7] Considering the clinical significance, aside of the classical description of AA branches, familiarity with different variations is also important.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] In case of injuries of the anterior chest wall, the AA and its branches may also be involved, which may also require surgical intervention. [3][4][5][6][7] Considering the clinical significance, aside of the classical description of AA branches, familiarity with different variations is also important. Lack of knowledge can lead to difficulties for plastic surgery, orthopedic surgery, and vascular surgery professionals during procedures involving this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation